Perbanyakan Tunas Pisang Cavendish (Musa acuminata L.) Secara In Vitro dengan Penambahan Naphthalene Acetic Acid (NAA) dan Air Kelapa - Riza Linda, Erika mahfudza, Mukarlina (Universitas Tanjungpura, 2018)
Cavendish banana (Musa acuminata L.) is classified into Musaceae Family which is originally from Southeast Asian. The superiority of this banana is its size which is bigger and it has 10 hand of bananas. The addition of growth regulator (zpt) in the tissue culture medium is a vital component in the process of the growth and the development of the plants in vitro. This research aims at identifying the influence of NAA and coconut water toward the multiplication of cavendish banana through in vitro. The research was conducted for three months since January to March of 2017 in the local Laboratory of Regional Technical Implementation Unit (UPTD) of Aloe Vera Agribisness Centre (AVC) at Agriculture, Fishery, and Forestry Agency of the Pontianak, North Pontianak sub-district. The research empoyed a completely randomised design with four level factors of NAA (N) with concentration of 0 M (N1), 10-7 M (N2), 5x10-6 M (N3), 10-6 M (N4) and coconut water (A) with concentration of % (A1), 10% (A2), 15% (A3) and 20% (A4). The results show that the single N2 treatment could gain the average rates of crown and leaves by 9.33 and the treatment of N4A2 could provide the average rate of shoot by 1,33.